A Study on Quality of Work Life of Employees in Vardhman Knit Garments in Ludhiana District: Exploring Quality of Work Life in the Garment Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the modern era, with the rapid growth of technology, industrialization, and enhanced work pressure, stress management has become one of the most significant concepts in the professional arena. It is also seen that in order to improve the efficiency in work, the employees are sometimes unable to maintain a balance between their personal and professional lives. The high level of competition, multifarious responsibilities on the work and in personal life led the employees to face a lot of challenges and consequently in maintaining work-life balance. This has further led to increase the work life stress. The increased pressure on employees which had made organisations to take care of their employees. Therefore, organizations have to formulate employee centric policies that lead to better job performance, less job stress resulting to more job satisfaction. This degree of satisfaction has been referred to as Quality of Work Life (QWL). The study focuses on the key elements of Quality of Work Life like job performance, job security and employee satisfaction etc. The objectives of the study arc to study the employees’ perception about Quality of Work Life and to determine their overall Quality of Work Life in Vardhman Knit Garments. It is descriptive and exploratory study in nature. The pre-tested structured questionnaire has been used for the collection of primary data from the respondents. The company records, company website and various journals have collected as secondary data for the study. The sample size taken in the organization is around 150 employees and was selected by the convenience sampling method. The Simple percentage analysis, Chi square test have used by the researcher for analysis.